Cooperative Banking: A Viable Approach To Microfinance - A Case Study in the Philippines - Ben R. Qui\~nones (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1999)
A leading cooperative bank in the Philippines has demonstrated that cooperative banking can be a viable approach to microfinance. Established in May 1975, the Cooperative Rural Bank of Bulacan, Inc. (CRBBI) integrates the components of rural banking and cooperativism: it is a rural bank owned and controlled by 180 primary organizations in Bulacan. CRBBI was registered with the central bank, Bangko Sentral ng Pililipinas (BSP) as a stockholding company in April 20, 1978. It has an authorized capital stock of P10 million (263,158 at December 1998 exchange rate), of which P7.689M (202,342) or 77% have been subscribed and fully paid. Its Head Office is located in the municipality of Plaridel at the heart of Bulacan province, while its seven (7) branches are spread in other municipalities of the same province. CRBBI?s Board is composed of 11 members elected by the general assembly constituted by the Chairmen of primary organizations. The Board meets once a month together with some permanent invitees such as the Treasurer, the Secretary, the legal adviser, and the ex-Chairman who is retained as consultant to the bank.
Keywords: 330